Intervención del terapeuta respiratorio en paciente femenino de 63 años con neumonía adquirida en la comunidad. - Triana Cando, Aisha Antonela (2023)
In the clinical case of a 63-year-old patient with community-acquired pneumonia, in which the general objective was to analyze the intervention of the respiratory therapist in the care of a female patient. Community-acquired pneumonia is a disease that is characterized by being an acute infection of the lower respiratory tract, essentially affecting the alveoli, which suffer abnormalities such as the accumulation of secretions, it is one of the easiest pathologies to diagnose by means of radiological examinations due to the opacity that is evident. The importance of taking care of this pathology is based from the diagnostic method to the treatment that is going to be applied, which is essential in the intervention carried out by the respiratory therapy professional so that the patient overcomes this pathology, it must be managed accordingly. the most appropriate way and offer alternatives taking into account the patient's oxygenation, guaranteeing a permeable airway. In conclusion, it is important to indicate that the work of the respiratory therapist in this case was vital for the treatment of pneumonia, in this case respiratory maneuvers and activities were carried out to improve the patient's oxygen saturation.